17th AIAA Computational Fluid Dynamics Conference 2005
DOI: 10.2514/6.2005-4983
|View full text |Cite
|
Sign up to set email alerts
|

Pareto-Optimality-Based Constraint-Handling Technique and Its Application to Compressor Design

Abstract: A new constraint-handling technique based on Pareto-optimality concept is proposed for evolutionary algorithms to efficiently deal with multiobjective multi-constraint design optimization problems. The essence of the proposed method is to apply non-dominance concept based on constraint function values to infeasible designs and to apply nondominance concept based on objective function values to feasible designs. The proposed technique does not need any constants to be tuned as the proposed technique does not us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…For example, Oyama et al [7] conducted the optimization of the airfoil of an aircraft-like Mars explorer at a 2 deg angle of attack by using a twodimensional (2D) Reynolds-averaged Navier-Stokes simulation and genetic algorithms for maximizing the lift and minimizing the drag. Their result showed that cambered thin airfoils are obtained as a Pareto-optimal solution with maximum lift-to-drag ratio [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Oyama et al [7] conducted the optimization of the airfoil of an aircraft-like Mars explorer at a 2 deg angle of attack by using a twodimensional (2D) Reynolds-averaged Navier-Stokes simulation and genetic algorithms for maximizing the lift and minimizing the drag. Their result showed that cambered thin airfoils are obtained as a Pareto-optimal solution with maximum lift-to-drag ratio [8].…”
Section: Introductionmentioning
confidence: 99%
“…Esp. under the condition of multiple constraints, the MDO such as the HSRS system should adopt a dialectical and unifed analysis viewpoint [36], i.e., the hunting motion stabilization is conditional, which depends on the geometric nonlinearity of worn wheel-rail contact.…”
Section: Full-vehicle Stability Properties and Variation Patternsmentioning
confidence: 99%
“…The best-N strategy is used as an elitist strategy to accelerate convergence. To avoid having to use penalty functions, the Paretooptimality-based constraint handling technique [16] is incorporated in the genetic algorithm. After non-dominated solutions are obtained, the trade-off is analyzed by data mining methods.…”
Section: A Generalized Frameworkmentioning
confidence: 99%